A source model for the electron contamination of clinical linac heads in photon mode. - González-Infantes, Wilfredo; Anguiano, Marta; Lallena, Antonio (IOP, 2015)
In this work a general source model has been developed to describe the electron contamination in clinical linac heads when operating in photon mode. The model includes two-sources that take into account the electrons generated in the linac head and in the air gap between the linac head and the patient. Their geometrical characteristics are determined by fitting the model of total fluence distribution to a set of fluence data in air just before entering the water phantom and for various field sizes up to 40 × 40 cm2 . The electron energy distributions are fitted to those obtained from phase-space files calculated with PENELOPE at the patient surface and for the largest field size. To verify the model, percentage depth doses and transverse profiles in water obtained from a Monte Carlo simulation performed with a complete and detailed linac geometry are compared to those found with the source model. Six linacs (three operating at 6 MV, one at 15 MV and two at 18 MV) have been studied. A comparison with the results obtained with a single source model is also carried out. The two-source model proposed provides a reasonably good description of the dose absorbed in water for all irradiation fields considered. The largest differences occur at the entrance of the phantom, for the low energy configurations and the smaller fields, reaching ∼ 15% at most. The two-source model describes much better than the single source one the lateral profiles in depth.
https://publishingsupport.iopscience.iop.org/questions/what-is-iop-publishings-green-open-access-policy/
Keywords: Aceleradores lineales; Electrones; Electron source model; LINAC